(untitled) (Eurasian Scientific Herald, 2023)
To attract investments, it is necessary to demonstrate the investment potential of our country in every way. Investors must analyze the risks that may affect investment projects before investing in the conditions of the coronavirus crisis. Based on the above, it can be said that improving the methodology of analysis and assessment of investment project risks based on modern and best practices has become one of the current urgent tasks.